Design and Development of a Single-Axis Solar Tracking System - Bhuyain, Md. Taslim Mahmud; Kuri, Robin; Bhuiyan, Nayeem Al-Tamzid; Sagor, Md Sahadat Hossain; Haidar, Riazul (International Multidisciplinary Research Journal, 2021)
With solar tracking, it will become possible to generate more energy since the solar panel can maintain a perpendicular profile to the rays of the sun. Even though the initial cost of setting up the tracking system is considerably high, there are cheaper options that have been proposed over time. This research discuss the design and construction of a prototype for a solar tracking system that has a single axis of freedom. Light Dependent Resistors (LDRs) are used for sunlight detection. The control circuit is based on an ATMega328P microcontroller. It was programmed to detect sunlight via the LDRs before actuating the servo to position the solar panel. The solar panel is positioned where it is able to receive maximum light. As compared to other motors, the servo motors are able to maintain their torque at high speed. They are also more efficient with efficiencies in the range of 80-90%. Servos can supply roughly twice their rated torque for short periods. Through tracking, there will be increased exposure of the panel to the sun, making it have increased power output. The trackers can either be dual or single axis trackers. As a single tracking system is cheaper, less complex, and still achieves the required efficiency, so it was used.